2008
DOI: 10.1007/s10452-008-9217-4
|View full text |Cite
|
Sign up to set email alerts
|

Can acclimation of amphipods change their antioxidative response?

Abstract: The aim of this study was to evaluate whether experimental conditions, particularly duration of acclimation in the laboratory with artificial water and diet prior to the actual experiment, can affect the antioxidant response of amphipods. This issue was evaluated using the Baikalian amphipod Eulimnogammarus cyaneus (Dyb.) exposed to two sources of natural organic matter (NOM). NOM elicits several oxidative stress symptoms and we used peroxidase activity as a representative response parameter. Pretest acclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…A decrease in peroxidase activity at intermediate temperatures (±6 °C around the optimum) may reflect either a decrease in ROS production, or serve as an energy-saving mechanism that redirects resources to other protective mechanisms (e.g., chaperones) to ensure optimal cellular protection at high temperatures. A similar decrease in activities of antioxidant enzymes has been previously shown in response to a variety of environmental stressors in amphipods (Timofeyev et al, 2008; Timofeyev et al, 2009). No changes in activity of catalase and glutathione S-transferase were found in the freshwater or saltwater populations of amphipods.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A decrease in peroxidase activity at intermediate temperatures (±6 °C around the optimum) may reflect either a decrease in ROS production, or serve as an energy-saving mechanism that redirects resources to other protective mechanisms (e.g., chaperones) to ensure optimal cellular protection at high temperatures. A similar decrease in activities of antioxidant enzymes has been previously shown in response to a variety of environmental stressors in amphipods (Timofeyev et al, 2008; Timofeyev et al, 2009). No changes in activity of catalase and glutathione S-transferase were found in the freshwater or saltwater populations of amphipods.…”
Section: Discussionsupporting
confidence: 82%
“…Lower baseline levels of some antioxidants (such as catalase) and a lack of increase in antioxidant levels during heat stress in the saltwater amphipods may reflect the reliance of these organisms on other antioxidants, such as low molecular weight antioxidants obtained from the diet (Lesser, 2006). An earlier study showed that dietary antioxidants can strongly affect the degree and direction of the antioxidant response to environmental stressors in amphipods (Timofeyev et al, 2009). The differences in the predominant diet in amphipods from the saltwater and freshwater habitats could affect the tissue levels of non-enzymatic antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Timofeyev et al (2009) showed that laboratory acclimation of amphipods changed their antioxidant pattern when stressed by HSs. Since the most drastic change during the acclimation of the animals was in their diet, it is very likely that the lack of spontaneous antioxidants or an excess of carbon in the laboratory food were the main reason for the change.…”
Section: Humic Substances As Stressormentioning
confidence: 99%
“…As with many other stresses, the HS-mediated stress may also be overcome, at least partly, if the diet of the exposed animals contains spontaneous antioxidants, such as ascorbic acid. There are indications that different diets have a significant impact on the antioxidant response of aquatic invertebrates (Elser et al 2000;Jensen and Hessen 2007;Timofeyev et al 2009), particularly excess of carbon leads to oxidative stress (Darchambeau et al 2003).…”
Section: Introductionmentioning
confidence: 99%